Margins of multinational labor substitution - Marc-Andreas Mündler; Sascha O. Becker (Deutsche Bundesbank, 2006)
Multinational labor demand responds to wage differentials at the extensive margin, when a multinational enterprise (MNE) expands into foreign locations, and at the intensive margin, when an MNE operates existing affiliates across locations. We derive conditions for parametric and nonparametric identification of an MNE model to infer elasticities of labor substitution at both margins, controlling for location selectivity. Prior studies rarely found foreign wages or operations to affect employment. Our strategy detects salient adjustments for German MNEs. With a one-percent increase in German wages, German MNEs add 2,000 manufacturing jobs in Eastern Europe at the extensive margin and 4,000 jobs overall; a converse one-percent drop in Eastern European wages is associated with an overall withdrawal of 730 MNE jobs from Germany.
Keywords: F21; F23; C14; J23; C24; 330; Multinational enterprise; location choice; multiple sample selectivity; labor demand; translog cost function; nonparametric estimation; Multinationales Unternehmen; Betriebliche Standortwahl; Arbeitsnachfrage; Substitutionselastizität; Deutschland